Does social capital boost or block renewable energy siting? South African solar politics in comparison. (January 2021) - Fraser, Timothy
Abstract: Why do some towns host more renewable energy than others? This mixed-methods study uses policy adoption theory to test whether social resources, namely social capital, affect which localities adopt the most solar power plants, and whether social capital's effects vary by policy regimes, geography, or development. I focus on utility scale solar plants over 10 kW in installed capacity. Using GIS, statistical models, and qualitative case studies, I test what factors shape solar siting under seven policy regimes worldwide. I examine democratic, early adopters of renewable power in their regions, including auctions in South Africa (2011–2018), Germany (2014–2018), and California (2010–2018), contrasted with feed-in tariffs in Germany (2004–2008 and 2008–2011), Japan (2012–2017), and Vermont (2010–2018). I find that bridging social capital acts as an obstacle in several countries, including South Africa, regardless of a country's geography, development, or choice of feed-in tariff or auction policy. Better opportunities for public participation in siting could improve South Africa's chance for a just transition to renewable energy.